Violência contra a mulher e políticas públicas: a política de abrigamento na Paraíba - Chaves, Isabella Alencar Maroja (2017)
The problem of violence against women has gained increasing visibility and public policies have created various actions and measures to address them. Thus, the present study seeks to analyze the effectiveness of the shelter houses that make up the shelter policy of the state of Paraíba, from the point of view of women in situations of violence sheltered, in care, and out of the units. The shelters are public policies that are part of the services of the attendance network for women in situations of violence and are confidential, full-time and temporary places which have the purpose of welcoming women and their children in situations of violence and who are at risk of life, ensuring their physical and psychological integrity. Violence against women is here situated as a historical phenomenon, socially constructed and represents a serious social, legal, cultural and public health problem. In this way, the main public policies aimed at combating violence against women were identified, with emphasis on shelter policy in the form of shelter houses. Statistical data were also included with the numbers of violence against women at the national and state levels. The study used the qualitative approach and the instruments for data collection were documentary research and semi-structured interviews with sheltered, in care, and out of the units women, as well as with female employees who were part of the technical team of shelter houses. The results evidenced the presence of all kinds of violence (physical, psychological, moral, patrimonial and sexual) and shame, fear and humiliation are feelings that are found in almost every report. The work carried out by the shelters ensures safety and protection of sheltered women's lives, as well as educational actions that help them cope with the problem and understand the context of violence in their lives and the recognized joint effort so that, sheltered women may have work, housing and / or social benefits granted, as they leave. On the other hand, the reports identify a questioning in the sense of shelter, in the view of the sheltered, be understood as a prison and, thus, represent for these an unjust inversion between aggressorassaulted. Thus, the importance of carrying out educational actions in a constant manner, planned and articulated with all multidisciplinary technical staff and the need for post-shelter monitoring to evaluate the effectiveness of the actions carried out in shelter houses in the life of women after they left the unit.